The Black Sea in Secondary Use – About Transonymization of Hydronyms - Gola, Jolanta (Poznańskie Studia Slawistyczne, 2024)
The article is related to my scientific research in the previous stages of studies, i.e. master’s studies in Slavic studies in the field of Croatian studies and bachelor’s studies in Slavic studies in the field of Bulgarian studies – with vocabulary related to water topics. This article aims to: determine how many dehydronym lexemes Черно море (The Black Sea) exist in Bulgaria, verify which objects are given such proper names and check whether it is possible to observe the dependence of the given names on geographical space, i.e. whether transonyms derived from the hydronym Черно морe occur most often near the reservoir itself or on the outskirts of Bulgaria. As I prove in the following considerations, the hydronym Черно море is quite a common and willingly used proper name. As a result of the transonymization process, dehydronymous names are used secondarily and are used to name hodonyms, ojkonyms or chrematonyms. Both in Bulgarian and Polish, water names are quite expansive and are often better and more widely known than their hydronymous prototypes.